Strategi Pengelolaan Kelas yang Efektif dalam Meningkatkan Kualitas Pembelajaran di Sekolah Dasar - Nur Wahyuni; Fitria Ningsih; Nabira Anjani Fitri; Nabila Putri Utami (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
This study aims to conduct an in-depth study of various effective classroom management strategies at the elementary school level. Classroom management plays a crucial role in supporting the smooth running of the teaching and learning process, as a successful learning process is greatly influenced by a conducive, orderly, and enjoyable classroom environment. Teachers serve not only as transmitters of material but also as classroom managers tasked with creating a learning climate that supports active student engagement. Good classroom management is believed to minimize disruptions, improve discipline, and foster student motivation. The research method used is library research, reviewing various academic sources such as books, scientific articles, research journals, and relevant previous studies. This approach was chosen to obtain a comprehensive overview of classroom management strategies that have been proven effective in educational practice in elementary schools. The results of the study indicate that effective classroom management strategies encompass several key aspects. First, the development of clear and mutually agreed-upon classroom rules so that students understand the boundaries of expected behavior. Second, the use of varied learning methods to accommodate different student learning styles. Third, the provision of positive reinforcement as a form of appreciation for student behavior and achievement. Fourth, establish good communication between teachers and students to build mutual trust and increase active participation. Implementing these strategies has been proven to improve discipline, reduce learning barriers, and create a classroom environment conducive to the optimal development of children's potential. These findings are expected to serve as a practical reference for teachers, schools, and related parties in designing more effective, innovative, and sustainable classroom management.